Effect of mobile phone use on reading habits of private secondary school students in Oyo state Nigeria. (2014)
"The study reported survey results that revealed that reading for fun; reading in the library; and reading books with color and illustrations were among factors that affected reading habit among students. The survey also showed that students were not favorably disposed to reading at home and that some of them were forced to read by their parents. The study further revealed that almost all the respondents owned a mobile phone. The researchers recommend that software applications and teaching materials be harnessed for use on mobile phones such that Nigerian students would be able to read and learn using this equipment."